2016
DOI: 10.1037/pap0000052
|View full text |Cite
|
Sign up to set email alerts
|

Do splitting and identity diffusion have respective contributions to borderline impulsive behaviors? Input from Kernberg’s model of personality.

Abstract: Kernberg’s object relations model postulates that excessive splitting compromises the integration of the positive and negative poles of the representations of self and other, as well as their arrangement into more complex and hierarchically ordered structures such as the individual’s identity, resulting in identity diffusion. In adult functioning, splitting and diffuse identity are conceived as 2 close functional related constructs and associated to borderline impulsivity. The present paper proposes an empiric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…A recent study by Gagnon, Vintiloiu, and McDuff [82] has shown that it is possible to empirically study the unique contribution of the self-concept (emotionally related with the concept of the other) and the splitting on BPD impulsive behaviors as conceptualized in Kernberg’s model. Moreover, each personality dimension was shown to be related to a specific aspect of BPD impulsivity.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Gagnon, Vintiloiu, and McDuff [82] has shown that it is possible to empirically study the unique contribution of the self-concept (emotionally related with the concept of the other) and the splitting on BPD impulsive behaviors as conceptualized in Kernberg’s model. Moreover, each personality dimension was shown to be related to a specific aspect of BPD impulsivity.…”
Section: Discussionmentioning
confidence: 99%
“…Kernberg's theoretical assumptions and model of personality functioning have been the object of empirical scrutiny in recent years, and the relationship between PO, psychopathology, and PDs more specifically has been empirically supported in both clinical and non‐clinical adult populations (Ellison & Levy, 2012; Ensink, Rousseau, Biberdzic, Bégin, & Normandin, 2017; Gagnon, Vintiloiu, & McDuff, 2016; Pilarska & Suchańska, 2016; Sollberger & Walter, 2010; Stern et al, 2010; Yun, Stern, Lenzenweger, & Tiersky, 2013), with the construct of PO being used to measure structural aspects of personality functioning (Fischer‐Kern et al, 2010; Koelen et al, 2012). For example, in a clinical sample of patients with BPD, Sollberger and Walter (2010) found that BPD patients with high identity diffusion showed significantly higher levels of psychiatric symptoms, as well as higher anxiety, anger, and depression scores compared to BPD patients with lower identity diffusion.…”
Section: Personality Organizationmentioning
confidence: 99%
“…Splitting Index [37] The French version of the SI [25] is a 24-item self-report instrument designed to assess the defense mechanism of splitting, as described in the writings of Kernberg (e.g., [7]) on self and object representations. This self-report questionnaire was initially developed and validated on a population of university students.…”
Section: Methodsmentioning
confidence: 99%